2016
DOI: 10.1093/rpd/ncw257
|View full text |Cite
|
Sign up to set email alerts
|

Patient Dose in Fluoroscopically Guided Cervical Discectomy and Fusion

Abstract: Cervical discectomy and fusion (CDF) is a minimally invasive procedure, where the accurate placement of the implants is accomplished using fluoroscopic guidance. Therefore, the evaluation of the radiation dose becomes mandatory. The purpose of the current study was to assess patient dose during fluoroscopically guided anterior and/or posterior CDF procedures. Thirty-three patients undergoing single or multiple-level CDF were studied using a mobile C-arm system. Data regarding fluoroscopy time (FT), air kerma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 35 publications
1
23
2
Order By: Relevance
“…E may be calculated for interventional fluoroscopy examinations in different ways . In some publications, E is determined by using the irradiation geometry for the clinical protocol and radiation dose data for clinical procedures as inputs into a Monte Carlo radiation transport simulation that uses computational models of human anatomy . In other publications, the irradiation geometry for the clinical protocol and radiation dose data for clinical procedures are used as parameters for irradiation of physical anthropomorphic phantoms containing dosimeters .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…E may be calculated for interventional fluoroscopy examinations in different ways . In some publications, E is determined by using the irradiation geometry for the clinical protocol and radiation dose data for clinical procedures as inputs into a Monte Carlo radiation transport simulation that uses computational models of human anatomy . In other publications, the irradiation geometry for the clinical protocol and radiation dose data for clinical procedures are used as parameters for irradiation of physical anthropomorphic phantoms containing dosimeters .…”
Section: Methodsmentioning
confidence: 99%
“…30,35,41 In some publications, E is determined by using the irradiation geometry for the clinical protocol and radiation dose data for clinical procedures as inputs into a Monte Carlo radiation transport simulation that uses computational models of human anatomy. 9,[17][18][19]27,38,42,43 In other publications, the irradiation geometry for the clinical protocol and radiation dose data for clinical procedures are used as parameters for irradiation of physical anthropomorphic phantoms containing dosimeters. 37,[44][45][46] Published values of E in the literature are based on tissue weighting factors (w T ) from either International Commission on Radiological Protection (ICRP) Publication 60 47 or ICRP Publication 103.…”
Section: C Radiation Dose Quantitiesmentioning
confidence: 99%
“…In reviewing the literature there were limited studies looking specifically at radiation exposure during anterior cervical discectomy and fusion (ACDF) as this procedure already has a low radiation dose exposure per procedure (33)(34)(35). This shows that more study is required has the cumulative dose can still have been dramatic effects have there are increasing trends in ACDF being performed in the outpatient settings (36).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that more study is required has the cumulative dose can still have been dramatic effects have there are increasing trends in ACDF being performed in the outpatient settings (36). In a study by Metaxas, they demonstrated a low cumulative dose range of 0.96 mGy (range, 0.04−6.58 mGy) and ED between 0.001 and 0.097 mSv (average 0.015 mSv) (33). This study, however, has some limitations with the use of Caldose software which has no modality to estimate dose to the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…For cervical interventions, the patient ESD, thyroid absorbed dose (which is the most radiosensitive organ inside the x-ray field), as well as the ED were calculated according to the method used in a previous study [478].…”
Section: Dose Calculationsmentioning
confidence: 99%